Soybean seed quality: the impact of foliar application with molybdenum and nickel - Cardoso, Bruna Miguel [UNESP]; Dameto, Larissa Sartori; Delfim, Jorge; Cardoso Moraes, Larissa Alexandra; Lazarini, Edson [UNESP]; Moreira, Adônis (Universidade Estadual de Londrina, 2024)
Soybean have shown increasing performance in terms of productivity in recent years and adequate management of plants increase the physiological quality of a considerable share of seeds. The enriched with micronutrients, especially molybdenum (Mo) and nickel (Ni), can be an important strategy to increase seed yield. This study aimed to evaluate the effects of Mo and Ni foliar application on the nitrogen (N) content, quality of germination (root protrusion, aging in terms of vigor, germination, and seedling size), and size of soybean seeds grown under two soil and climate conditions. The treatments consisted of four application Mo rates (0, 400, 800, and 1600 g ha-1) and three Ni rates (0, 60, and 120 g ha-1) applied at the beginning of the reproductive stage (R1 and R2). The experiments were at Londrina (Brasmax Desafio RR), and Selviria (TMG 7063 IPRO, and Brasmax Desafio RR). Root protrusion, vigor, and seedling size were influenced by the foliar Mo application, whereas Ni application at a high rate decreased root protrusion. The foliar Mo application influenced the seed N content, seed size, and physiological quality of seeds with the 800–1600 g ha-1
Qualidade da semente de soja: impacto da aplicação foliar com molibdênio e níquel
Keywords: Germination; Glycine max; Root protrusion; Seed size; Vigor